Study on laser powder bed fusion of nickel-base alloy of G-surface structure: scanning strategy, properties and compression properties - Bo Qian (Nature Portfolio, 2021)
Abstract Aiming at laser powder bed fusion of GH3536 nickel base alloy, the effects of different scanning strategies on microstructure, porosity and mechanical properties were explored. In the aspect of microstructure and micro hardness of the sample, three scanning strategies had little difference; in the aspect of macro mechanical properties of the sample, the slope subarea scanning was better than the helix and island scanning. On this basis, the slope subarea scanning was selected as the optimal scanning strategy to form the G-surface structure, and the compression performance of G-surface was studied. The results showed that: (1) the compression performance of G-surface structure was smaller than that of solid structure, The compression strength of G-surface can only reach about 20% of solid structure: the average strength value of G-surface is 220 MPa, solid structure is 1.1 GMpa; while G-surface structure had a smooth compression curve, which indicated the good energy absorption characteristics; (2) with the increase of wall thickness, the mechanical performance of G-surface structure was also enhanced, while the energy absorption capacity was constantly reduced; (3) with the same wall thickness, the compression performance of sample in building direction (BD) is higher than that in horizontal direction (HD).